(untitled) (Malaysian Journal of Civil Engineering, 2018)
The use of composite materials such as fiber-reinforced polymers in strengthening and repairing of reinforced concrete elements is widely spreading. However, for successful and costeffective applications, engineers must improve their knowledge with respect to the actual behavior of strengthened structures. The CFRP sheets used in strengthening applications have high strength; however, they are brittle materials with low ductility. Basalt fiber reinforced polymer (BFRP) sheets on the other hand have relatively lower strength compared to CFRP, however they have higher ductility and cheaper than carbon fibers. As a result, there is growing interest among researchers and practitioners in combining different types of FRP sheets to produce an enhanced strengthening system in terms of strength and ductility. This hybrid system is designed to enhance the properties of composites, where it combines the high strength of CFRP and high ductility of BFRP sheets, respectively. This paper presents the nonlinear finite element analysis (FEA) that has been carried out to simulate the behavior of failure modes of reinforced concrete (RC) beams strengthened in flexure using CFRP sheets, BFRP sheets, and their hybrid combination (CFRP-BFRP). Besides, new technical approach is presented numerically to show that concrete cover replacement with high strength concrete one provided better load capacity and failure mode, indicating utmost utilize of the hybrid combination of CFRP-BFRP in strengthening of RC beams. The commercial and general finite element analysis; ABAQUS software is used for modeling and nonlinear analysis. Load deflection relationships, failure mode, ductility, ultimate load and ultimate deflection were obtained and compared with the recent experimental results available in literature. From the analysis, it is found that FEA can predict accurately the load-displacement relation and good agreements were obtained when compared to the experimental data. In addition, the proposed FE analysis can be reliably used as a cost-effective tool to predict the inelastic behavior of strengthened beams.